2010
DOI: 10.1007/s10637-010-9568-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel histone deacetylase inhibitor CG200745 induces clonogenic cell death by modulating acetylation of p53 in cancer cells

Abstract: Histone deacetylase (HDAC) plays an important role in cancer onset and progression. Therefore, inhibition of HDAC offers potential as an effective cancer treatment regimen. CG200745, (E)-N(1)-(3-(dimethylamino)propyl)-N(8)-hydroxy-2-((naphthalene-1-loxy)methyl)oct-2-enediamide, is a novel HDAC inhibitor presently undergoing a phase I clinical trial. Enhancement of p53 acetylation by HDAC inhibitors induces cell cycle arrest, differentiation, and apoptosis in cancer cells. The purpose of the present study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
1
28
0
1
Order By: Relevance
“…1), which has entered phase I clinical studies in Korea on 31 May 2010. It was reported that CG200745 induces cell death by modulating acetylation of p53 [24].…”
Section: Introductionmentioning
confidence: 99%
“…1), which has entered phase I clinical studies in Korea on 31 May 2010. It was reported that CG200745 induces cell death by modulating acetylation of p53 [24].…”
Section: Introductionmentioning
confidence: 99%
“…The above results suggest that TSA induce cell cycle arrest in CRC cells through p53-dependent and -independent pathway. Some HDAC inhibitors, including TSA, have been reported to induce apoptosis in cancer cells through activation of p53 by phosphorylation or acetylation (24,25), suggesting a p53-dependent apoptotic pathway by TSA. Here, we showed that TSA was effective in both p53 wild-type HCT116 cells and p53 mutant HT29 cells, indicating that TSA could induce apoptosis in CRC cells via both p53-dependent and -independent mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the acetylation effects on histone H3, CG200745 acetylated p53 and induced its accumulation, leading to p53 transactivation and clonogenic cell death. However, the effects of CG200745 on p53 acetylation using cells transfected with various p53 mutants showed that cells expressing p53 K382R mutants were significantly resistant to CG200745-induced clonogenic cell death compared to wild-type p53 cells [3]. CG200745 also showed increased histone H4 acetylation and apoptosis in vitro and in vivo with HCT116 colon cancer models [4].…”
Section: Introductionmentioning
confidence: 99%